Procedure for Safe Distance Determination for Minor Movement Accomplishing at Unsignalized Intersections - Vuk Bogdanović; Ivan Dadić; Zoran Papić; Nenad Ruškić (Promet - Traffic&Transportation, 2012)
A minor movement performed at unsignalized intersections is one of the most complex and most difficult actions in traffic. Drivers performing a minor movement make decisions based on the estimation of movement parameters of vehicles in the major street. A driver’s estimation depends on subjective estimation of the distance between vehicles in the major street and the gap which exists between them, that is, the time gap in the conflicting flow which is suitable for accomplishing a minor movement. The possibilities of estimation are sometimes limited due to complex traffic conditions, as well as the limited driver’s view. When, during doing a minor movement, a traffic accident happens, in most cases the cause of the accident is the failure to give right-of-way. But, in case when a vehicle from the major street moves at a speed above the limited one, based on the existing analytical procedures, it is impossible to determine the extent of their responsibility. This paper shows the procedure for safe distance determination, necessary for accomplishing a minor movement, as well as the procedure of establishing the driver’s omission, depending on the movement regime and traffic conditions at unsignalized intersections.